2019
DOI: 10.1007/s10120-019-01016-9
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the one-step nucleic acid amplification assay in sentinel node mapping for early gastric cancer patients

Abstract: Background To safely perform minimized gastrectomy based on sentinel node (SN) concept for early gastric cancer patients, intraoperative diagnostic accuracy is indispensable. This study aimed to evaluate the clinical utility of the one-step nucleic acid amplification (OSNA) assay in the intraoperative diagnosis of SN metastasis in early gastric cancer patients compared with that of histopathological examination. Methods We conducted a prospective study using the OSNA assay for 43 patients with cT1N0M0 gastric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Moreover, in the current study, SLNs had to be identified in the unfixed state. While the original protocol achieved results that were comparable with the favorable results of Japanese authors using in-vivo SLN mapping [ 23 , 25 ], this was not true in the current study. The efficacy of the protocol was too low to enable restricting the analysis to the identified SLNs.…”
Section: Discussionmentioning
confidence: 39%
See 3 more Smart Citations
“…Moreover, in the current study, SLNs had to be identified in the unfixed state. While the original protocol achieved results that were comparable with the favorable results of Japanese authors using in-vivo SLN mapping [ 23 , 25 ], this was not true in the current study. The efficacy of the protocol was too low to enable restricting the analysis to the identified SLNs.…”
Section: Discussionmentioning
confidence: 39%
“…To the best of our best knowledge, this is the first study outside Japan to apply the OSNA technique for LN analysis in gastric cancer. The high efficacy of OSNA in detecting LN metastases has been shown in former studies from Japan ( Table 3 ) [ 22 , 23 , 24 , 25 ]. Therefore, it was the aim of this study to evaluate OSNA in a European center, where it is unusual to perform post-operative LN dissection in the unfixed state.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Reaction mixture contained tree pairs of primers: 5′-GGAGTTCTCAATGGTGGCACCAACTACTACACGACCATCCA-3′ (CK19 forward inner primer), 5′-GTCCTGCAGATCGACAACGCCTCCGTCTCAAACTTGGTTCG-3′ (CK19 reverse inner primer), 5′-TGGTACCAGAAGCAGGGG-3′ (CK19 forward outer primer), 5′-GTTGATGTCGGCCTCCACG-3′ (CK19 reverse outer primer), 5′-AGAATCTTGTCCCGCAGG-3′ (CK19 forward loop primer), and 5′-CGTCTGGCTGCAGATGA-3′ (CK19 reverse loop primer) [ 16 ]. The RT-LAMP method measured the time taken to exceed a predetermined threshold turbidity caused by magnesium pyrophosphate, which is a by-product of the amplification reaction [ 17 ]. The change in turbidity correlates with the CK19 mRNA copy number calculated from the value of the standard curve, which was previously determined with three calibrators containing different concentration of CK19 mRNA copy number/µL [ 14 , 18 ].…”
Section: Methodsmentioning
confidence: 99%